Local increase in IgE and class switch recombination to IgE in nasal polyps in chronic rhinosinusitis. Issue 5 (May 2014) - Baba, S.; Kondo, K.; Toma‐Hirano, M.; Kanaya, K.; Suzukawa, K.; Ushio, M.; Suzukawa, M.; Ohta, K.; Yamasoba, T.
Summary Background Chronic rhinosinusitis with nasal polyps is generally characterized by local Th2 inflammation and is categorized into two subtypes in Japan: eosinophilic chronic rhinosinusitis (similar to chronic rhinosinusitis with nasal polyps in western countries) and non‐eosinophilic chronic rhinosinusitis (characterized by Th1‐dominant inflammation). Objective To investigate local IgE production and class switch recombination to IgE in these two subtypes of chronic rhinosinusitis with nasal polyps. Methods The identity of IgE‐positive cells was determined using double‐immunofluorescent staining for IgE and cell‐type‐specific molecular markers. To investigate the local class switch recombination to IgE and IgE synthesis in the mucosa, we performed real‐time polymerase chain reaction to examine the mRNA expression of Th2 cytokines and class‐switch‐related molecules, including IL‐4, IL‐5, IL‐13, ε germline gene transcripts, IgE mature transcript, IgG mature transcript, RAG1, RAG2 and activation‐induced cytidine deaminase in eosinophilic polyps, non‐eosinophilic polyps and controls. Results The concentrations of total IgE and number of IgE‐positive cells were significantly higher in the eosinophilic polyps compared with control and non‐eosinophilic polyps. IgE‐positive cells were predominantly mast cells in eosinophilic polyps and significantly correlated with the number of FcεR1‐positive cells in the subepithelial layer. IL‐5 and IL‐13 mRNA and ε germline gene transcripts expression levels were significantly higher in eosinophilic polyps compared with control and non‐eosinophilic polyps. In contrast, the number of plasma cells and the expression of IgG mature transcripts were increased in non‐eosinophilic polyps compared with eosinophilic polyps. RAG2 mRNA was significantly increased in both eosinophilic and non‐eosinophilic polyps compared with control mucosa. Conclusion and Clinical Relevance The current study suggests local class switching to IgE, production of IgE and IgE localization to the surface of mast cells in eosinophilic chronic rhinosinusitis in the Japanese population. The difference in the IgE‐related profiles between eosinophilic chronic rhinosinusitis and non‐eosinophilic chronic rhinosinusitis suggests heterogeneity in the pathogenesis of chronic rhinosinusitis with nasal polyps.